Glutamine supplementation attenuates bisphenol a-induced testicular toxicity in rats - Ben E Ehigiator; Elias Adikwu; Zellijo N Igweze (Wolters Kluwer Medknow Publications, 2022)
Background: The induction of testicular toxicity by bisphenol A (BPA) may involve oxidative stress. Glutamine (Gln) is a rate limiter for the synthesis of glutathione (GSH), which inhibits oxidative stress. Aim: This study assessed the potential of BPA to preserve testicular structure and function in BPA-treated albino rats. Study Settings and Design: Thirty-two adult male albino rats (210-250 g) were randomly allocated to 4 (A-D) of 8 rats per group with the approval of the Research Ethics Committee. Materials and Methods: Groups B-D were orally treated with Gln (20 mg/kg body weight), BPA (50 mg/kg body weight) and Gln (20 mg/kg body weight) + BPA (50 mg/kg body weight) daily for 65 days, respectively. Group A (control) was orally treated with normal saline (0.2 mL) daily for 65 days. At the termination of treatment, the rats were weighed and anaesthetized blood samples were collected and evaluated for gonadal hormones. The testes were weighed and evaluated for sperm parameters, oxidative stress markers and histology. Statistical Analysis Used: The data were analysed using one-way analysis of variance and Bonferroni post hoc test. Results: BPA caused a significant (P < 0.001) decrease in testis and body weights, sperm count, volume, motility and normal morphology when compared to the control. BPA significantly (P < 0.001) decreased serum testosterone, follicle-stimulating hormone, luteinising hormone, testicular catalase, superoxide dismutase, GSH and GSH peroxidase levels relative to control. Significantly (P < 0.001) increased serum prolactin, estradiol and testicular malondialdehyde levels occurred in BPA-treated rats relative to control. The testes of BPA-treated rats showed sloughing and coalescence of germ cells. However, Gln supplementation prevents BPA-induced testicular toxicity. Gln supplementation restored testis histology. Conclusion: Based on the observation in this study, Gln seems effective against BPA-induced testicular toxicity.